2019
DOI: 10.1016/j.bbrc.2019.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces senescence in breast cancer stem cells

Abstract: Cancer stem cells (CSCs) have been shown to be resistant to current anticancer therapies and the induction of oxidative stress is an important mechanism of action for many anticancer agents. However, it is still largely unknown how CSCs respond to hydrogen peroxide (H 2 O 2)-induced oxidative stress. Here, we show that the levels of reactive oxygen species (ROS) are markedly lower in breast CSCs (BCSCs) than that in non-cancer stem cells (NCSCs). A transient exposure of breast cancer cells to sublethal doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…In 2005, Ostrakhovitch et al demonstrated that activation of p53 played a crucial role in copper and zinc-induced generation of ROS in epithelial breast cancer cells via its target genes such as p53-induced gene 3 product (PIG3) and BAX [309]. Oxidative stress could also upregulate p53 to induce senescence in breast cancer cells [310]. P53 was found to be essential in PARP-mediated necrotic cell death induced by ROS in breast cancer cells [311].…”
Section: P53 In Breast Cancermentioning
confidence: 99%
“…In 2005, Ostrakhovitch et al demonstrated that activation of p53 played a crucial role in copper and zinc-induced generation of ROS in epithelial breast cancer cells via its target genes such as p53-induced gene 3 product (PIG3) and BAX [309]. Oxidative stress could also upregulate p53 to induce senescence in breast cancer cells [310]. P53 was found to be essential in PARP-mediated necrotic cell death induced by ROS in breast cancer cells [311].…”
Section: P53 In Breast Cancermentioning
confidence: 99%
“…The development of drug resistance is a challenge for the use of adjuvant therapies in breast cancer patients [69], and studies suggest that ROS may play an important role in the production of drug-resistant cells [70]. Zhong et al demonstrated that oxidative stress and H 2 O 2 treatment led to a marked increase in senescence-associated β-galactosidase activity but only to minimal apoptotic cell death in CSCs, suggesting that ROS triggered the induction of senescence and exhibited therapeutic potential in the eradication of drug-resistant CSCs [8]. However, the increase in ROSs induced by drugs seems to play a different role compared to the role of ROS originally generated in malignant tumors.…”
Section: The Role Of Ros In the Occurrence And Development Of Breast mentioning
confidence: 99%
“…Recent studies have shown that reactive oxygen species (ROS) are involved in the molecular mechanisms of breast cancer occurrence and development [7][8][9]; ROS can be regulated by glutathione peroxidases (GPxs), which are the key enzymes that maintain ROS homeostasis in vivo through the reduction of ROS [10]. Therefore, based on summaries of the research regarding the relationship between breast cancer and GPxs, this article focused on the molecular mechanism and function of different GPxs and their diverse roles in the occurrence and development of breast cancer, further clarifying the pathogenesis of breast cancer and providing a potential…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cells seem to possess a lower ROS level than nontumoral stem cells, due to different mechanisms useful to reduce oxidative stress and maintain stem cell properties (404,(407)(408)(409). However, there are controversial aspects in the metabolism regulation of CSCs.…”
Section: Oxidative Stress and Cscsmentioning
confidence: 99%
“…On the other hand, as it has been mentioned above, ROS is related to several cancer-promoting effects, thus it might be advantageous to reduce ROS levels or increase antioxidant molecules, in order to restore de redox balance in the cell. For these reasons, the efficacy of these anticancer strategies depends on the ROS level in the tumor type and the capacity of the tumor to modulate its metabolism routes (404,409,(412)(413)(414)(415)(416)(417)(418)(419).…”
Section: Oxidative Stress and Cscsmentioning
confidence: 99%